Akses Keadilan bagi Korban Rudapaksa: Tinjauan Kritis terhadap Sistem Peradilan Pidana Indonesia dari Sudut Pandang HAM - Sanusi Sanusi; Rezike Nurul Ergiarti; Fajar Ari Sudewo; Mukhidin Mukhidin; Moh. Taufik (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study critically examines access to justice for minors who are victims of rape in the context of the Indonesian criminal justice system, with a special focus on the human rights (HAM) perspective. This study is motivated by the high number of cases of sexual violence against children and the complexity of handling them in the Indonesian legal system. The research problem is how to protect human rights for minors who are victims of rape in the law enforcement system in Indonesia. The research method uses qualitative normative legal research by analyzing legal doctrine and related legislation. The research method used is qualitative normative legal research, namely examining various laws and regulations and related literature to understand legal principles and their implementation in the field. The results of the study show that in terms of legal-normative, the protection of children's human rights is regulated in various national and international laws and regulations. However, there are several challenges in its implementation in the field such as limited understanding of law enforcement officers, facilities, and implementing regulations. For this reason, it is necessary to strengthen socialization, legal frameworks and implementation facilities, and continuous evaluation in order to realize universal protection of children's human rights. This study identifies systemic challenges faced by victims in seeking justice, including child-unfriendly legal procedures, lack of psychosocial support, and persistent social stigma. The main findings of this study indicate a significant gap between international human rights standards on child protection and practice on the ground. This study argues for a comprehensive reform of the Indonesian criminal justice system to better accommodate the needs and rights of child victims, including the provision of specialized legal assistance, increased sensitivity of law enforcement officers, and the development of a justice mechanism that focuses on recovery. This study offers concrete recommendations for system improvement, which are expected to serve as a reference for policymakers, legal practitioners, and other stakeholders in efforts to improve access to justice for child rape victims in Indonesia.